Intramuscular versus intravenous oxytocin for the third stage of labor after vaginal delivery to prevent postpartum hemorrhage: a meta-analysis of randomized controlled trials. (July 2020) - Zhou, Yuan-hong; Xie, Yan; Luo, You-Zhen; Liu, Xiao-Wen; Zhou, Jun; Liu, Qiang
Abstract: Introduction: To examine the effects and safety of oxytocin administered intramuscularly or intravenously for preventing postpartum hemorrhage (PPH) in the third stage of labor after vaginal deliveries. Material and methods: Before data extraction, the review was registered with the PROSPERO International Prospective Register of Systematic Reviews (registration No. CRD42019145912). We searched the published electronic databases, including Medline, EMBASE, PubMed, Web of Science, CNKI, VIP, Wanfang, the Cochrane Library, clinicaltrial.gov and PROSPERO database, from their inception until February 2019. We included all randomized controlled trials (RCTs) comparing intramuscular and intravenous oxytocin administered just after the birth of the anterior shoulder or soon after the birth of the baby during a vaginal delivery. The primary outcomes were the incidence of PPH and severe PPH. PPH was defined as a blood loss ≥500 ml within 24 hours after vaginal birth. Severe PPH refers to a clinically estimated blood loss equal to or greater than 1000 mL within 24 hours after vaginal birth. Statistical heterogeneity was assessed by the I 2 test, the Cochran Q statistic and the Galbraith plot for heterogeneity. Results: Six RCTs, including 7320 women undergoing vaginal delivery, were identified in the meta-analysis. Women who were randomized to have intravenous oxytocin for the third stage of labor had a significantly lower incidence of PPH (relative risk 1.35, 95% CI 1.11-1.64, p = 0.003), severe PPH (relative risk 1.61, 95% CI 1.05-2.46, p = 0.03) and blood transfusion (relative risk 2.50, 95% CI 1.37-4.59, p = 0.003) compared with those who were randomized to have intramuscular oxytocin during the third stage of labor after vaginal delivery. There was no significant difference with regard to changes in hemoglobin level, third stage of labor duration, mean postpartum blood loss, or the incidences of a need for additional uterotonics and of retained placenta or manual removal of placenta between groups. Conclusions: For women in the third stage of labor who are undergoing a vaginal delivery, the use of intravenous oxytocin reduces the incidence of PPH, severe PPH and blood transfusion and does not increase the risk of adverse effects compared with intramuscular oxytocin.